ASSOCIATION OF MICROFOCUSED ULTRASOUND AND POLY-L-LACTIC ACID AS COLLAGEN BIOSTIMULATORS: A STEREOPHOTOGRAMMETRIC EVALUATION - Patta Pereira, Izabella; Januzzi Santos, Marcelo (Health and Society, 2023)
Facial aging is a gradual process that involves a complex interaction of several factors, including loss of subcutaneous volume, deep bone resorption and tissue laxity. To promote rejuvenation, it is extremely important to restructure the multiple layers of the face, initially by inducing collagen synthesis and tissue contraction. Thus, the combination of Poly-L-lactic Acid and Microfocused Ultrasound has proven to be increasingly effective for treating flaccidity and as a collagen biostimulating technique. This study carried out a stereophotogrammetric analysis with the 3D Vectra H2 software of a clinical case of association of Microfocused Ultrasound (Classys) with Poly-L-lactic acid (Sculptra - Galderma) at the beginning of the treatment and 60 days later.